2022
DOI: 10.1029/2021gb007289
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric N Deposition Significantly Enhanced Soil N2O Emission From Eastern China Forests

Abstract: Nitrous oxide (N 2 O) is a long-lived greenhouse gas (GHG). Its global warming potential is ∼265 times that of CO 2 over a 100 year time horizon (IPCC, 2013). In addition, N 2 O is a dominant ozone-depleting substance that is not regulated by the Montreal Protocol (Ravishankara et al., 2009). On a global scale, natural soils are the largest source of atmospheric N 2 O (H. Tian et al., 2020). Exogenous nitrogen (N), such as the deposited reactive N, is transformed during the nitrification and denitrification pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 102 publications
2
1
0
Order By: Relevance
“…S8 ). Previous studies based on a meta‐analysis [ 44 ], a conceptual model [ 29 ], and an ensemble of terrestrial biosphere model showed that atmospheric N deposition enhances natural soil N 2 O emissions [ 45 ], which was consistent with our results. Apart from the effect of atmospheric N deposition, climate change leaded to an increase of 1.6 Gg N 2 O yr −1 for soil N 2 O emissions ( Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…S8 ). Previous studies based on a meta‐analysis [ 44 ], a conceptual model [ 29 ], and an ensemble of terrestrial biosphere model showed that atmospheric N deposition enhances natural soil N 2 O emissions [ 45 ], which was consistent with our results. Apart from the effect of atmospheric N deposition, climate change leaded to an increase of 1.6 Gg N 2 O yr −1 for soil N 2 O emissions ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Apart from the autotrophic nitrification and denitrifier denitrification considered in the DyN-LPJ model, the IBIS-MicN model included additional N 2 O-producing processes of heterotrophic nitrification and nitrifier denitrification [ 24 ], therefore, the IBIS-MicN model performed with a much smaller inter-annual variability. Both natural N 2 O emissions from forests and grasslands in this study are within the range of previous reports using the direct extrapolation method [ 25–28 ], linear models [ 29 ], random forest regression model [ 30 ], or process-based models [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 83%
“…It is important to note that maximizing soil CH 4 uptake might suggest maintaining a relatively high N deposition level around the transition point between Stage I and Stage II. However, this approach should consider the potential acceleration of N 2 O emissions resulting from N deposition (Cen et al., 2022). Further research is required to evaluate whether maintaining a relatively high N deposition rate can effectively reduce the gross greenhouse gas emissions.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach should consider the potential acceleration of N 2 O emissions resulting from N deposition (Cen et al, 2022). Further research is required to evaluate whether maintaining a relatively high N deposition rate can effectively reduce combined greenhouse gas emissions from soils.…”
Section: Suppressing Effect Of N Deposition On Global Soil Ch 4 Uptak...mentioning
confidence: 99%